Utilization of Mata Allo Enrekang River Aggregate as a Concrete Mixer - Ellen Kristin Pangloli; Herman Parung; Junus Mara (Paulus Civil Engineering Journal, 2022)
Mata Allo River is located in Enrekang, South Sulawesi. a river that has a fairly abundant source of aggregate material that has been used by the local community as a concrete-making material in the construction of small-scale construction. This study aims to determine the development of concrete strength based on concrete compressive strength, split tensile strength, flexural strength, and modulus of elasticity in normal quality concrete mixtures based on variations in the Water Cement Factor (FAS), namely Variations 0,49, 0,52 and 0,55 where the variation with the highest compressive strength is used to further testing. The Mix Design method used is the American Concrete Institute (ACI) method with a design concrete quality of 25 MPa. From the results of the study, the highest strength value was found in the FAS variation of 0,49 with an average compressive strength of 7 days, 14 days, 21 days, and 28 days, respectively, with a compressive strength of 16,977 MPa, 23,301 MPa, 25,276 MPa, and 26,691 MPa. The results of the research carried out, the characteristics produced from the Mata Allo river meet the SNI specification standard to be used as a concrete mixture.